Single-Nucleotide Polymorphisms in MICA and MICB Genes Could Play a Role in the Outcome in AML Patients after HSCT - Machuldova, Alena; Houdova, Lucie; Kratochvilova, Katerina; Leba, Martin; Jindra, Pavel; Ostasov, Pavel; Maceckova, Diana; Klieber, Robin; Gmucova, Hana; Sramek, Jiri; Holubova, Monika (Journal of clinical medicine, 2021)
NKG2D and its ligands, MICA and MICB, are known as the key regulators of NK cells. NK cells are the first reconstituted cells after the allogeneic hematopoietic stem cell transplantation (HSCT); therefore, it is crucial to understand their role in HSCT outcome. In the presented study, we investigated the single amino acid changes across the exons 2-4 of MICA and MICB genes, and point mutations within the NKG2D gene, which defines the type of NKG2D haploblock (HNK/LNK) in the donors (n = 124), as well as in patients with acute myeloid leukemia (n = 78). In our cohort, we found that graft from a donor with at least one MICA allele containing glycine at position 14 (MICA-14Gly) is significantly associated with deterioration of a patient's overall survival (OS) (p < 0.05). We also observed a negative effect of MICB-58 (Lys → Glu) polymorphism on relapse-free survival (RFS), although it was not statistically significant in multivariate analysis (p = 0.069). To our knowledge, this is the first work describing the role of MICA-14 and MICB-58 polymorphisms on HSCT outcome.
Keywords: MICA; NK cells; graft-versus-tumor effect; MICB; graft-versus-host disease; NKG2D; allogeneic hematopoietic cell transplantation